ANALYSIS OF INVESTMENT FACTORS WHICH ARE INFLUENCING THE GROWTH OF THE REPUBLIC OF SERBIA - Milojević, Ivan; Ignjatijević, Svetlana; Đorđević, Dragomir (Economics of Agriculture, 2016)
The subject of this research is empirical analysis of the factors which have influence on economic growth, whereas the main aim is to suggest adequate ways to overcome problems. We have analyzed the influence of budget defcit, personal consumption, inflation, real exchange rate, foreign trade balance and foreign direct investments (FDI) on economic growth. Furthermore, we measured the influence factors on the presence and movement of the budget defcit. Research paper uses the data obtained from the Statistical Offce of the Republic of Serbia, World Bank and the IMF for the time period 2001-2011 and has been applied regression analysis method. Research results indicate that the real exchange rate, personal consumption and foreign trade balance are statistically signifcant for anticipating economic growth developments. Contrary to our expectations, the empirical analysis showed that FDI have a negative influence on the economic growth. The coeffcient "public debt" is statistically signifcant and has a positive influence on the increase of budget defcit, whereas the increase of SDI and trade openness triggers a decrease in budget defcit. This research starts from the hypothesis that fnancing defcit limits economic growth and the inflow of FDI cant provide long-term economic growth. In the coming period Serbia needs to take advantage of the available resources and managing public fnances, obeying laws and regulations and continuing with reforms are fundamental for achieving a stable business environment.